2004
DOI: 10.1074/jbc.m406149200
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Control of the Antimicrobial Peptide Resistance ugtL Gene by the Salmonella PhoP and SlyA Regulatory Proteins

Abstract: The PhoP/PhoQ two-component system is a master regulator that governs the ability of Salmonella to cause a lethal infection in mice, the adaptation to low Mg 2؉ environments, and resistance to a variety of antimicrobial peptides. We have recently established that the PhoP-activated ugtL gene is required for resistance to the antimicrobial peptides magainin 2 and polymyxin B. Here we report that ugtL transcription requires not only the PhoP protein but also the virulence regulatory protein SlyA. The PhoP protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
128
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 39 publications
10
128
1
2
Order By: Relevance
“…The findings reported in this article provide further support to the notion that the PhoP͞PhoQ two-component system is a central regulator that controls the expression and͞or activity of other regulatory proteins and systems when cells experience low Mg 2 , including the two-component system RstA͞RstB of E. coli, (47), the Salmonella SpiR͞SsrB two-component system (48), and the Salmonella transcription factor SlyA (49). In addition, the PhoP͞PhoQ system has the ability to activate the PmrA͞PmrB system posttranslationally by promoting expression of the small basic protein PmrD (50), which has been shown to bind to the phosphorylated form of the response regulator PmrA protein and protect it from dephosphorylation by the sensor protein PmrB (51).…”
Section: Discussionsupporting
confidence: 73%
“…The findings reported in this article provide further support to the notion that the PhoP͞PhoQ two-component system is a central regulator that controls the expression and͞or activity of other regulatory proteins and systems when cells experience low Mg 2 , including the two-component system RstA͞RstB of E. coli, (47), the Salmonella SpiR͞SsrB two-component system (48), and the Salmonella transcription factor SlyA (49). In addition, the PhoP͞PhoQ system has the ability to activate the PmrA͞PmrB system posttranslationally by promoting expression of the small basic protein PmrD (50), which has been shown to bind to the phosphorylated form of the response regulator PmrA protein and protect it from dephosphorylation by the sensor protein PmrB (51).…”
Section: Discussionsupporting
confidence: 73%
“…We began by investigating Yersinia's ability to promote transcription of the S. enterica mgtA and ugtL genes, which have no orthologs in Y. pestis and harbor distinct promoter architectures (Fig. 1A) (21)(22)(23). Y. pestis produced fluorescence levels similar to those of S. enterica when transcription of a promoterless gfp gene was driven by the promoter of the mgtA gene (Fig.…”
Section: Differential Ability Of the Yersinia Phop Protein To Expressmentioning
confidence: 99%
“…The upper band in H-I corresponds to treR, a PhoP-repressed transcript going in the reverse orientation (22). The upper band in K and L corresponds to a spurious transcript observed in vitro but not in vivo (21,45). Quantification of the in vitro transcription assays is shown in J for mgtA and in M for ugtL.…”
Section: Differential Ability Of the Yersinia Phop Protein To Expressmentioning
confidence: 99%
“…In Salmonella enterica serovar Typhimurium, this transcriptional regulator modulates the intracellular expression of genes required for growth in macrophages (1) as well as bacterial resistance to cationic antimicrobial peptides (2,3) and to oxidative stress (4). Transcription of the slyA locus is activated by the PhoP/PhoQ 2-component system (2,5), which responds to different environmental signals including low-Mg 2ϩ , host-derived antimicrobial peptides, and acidic pH (6)(7)(8). Consistently, results from different laboratories showed that SlyA regulates a subset of PhoP-dependent genes, including ugtL and pagC, in Salmonella (2,3,(9)(10)(11).…”
mentioning
confidence: 99%
“…Transcription of the slyA locus is activated by the PhoP/PhoQ 2-component system (2,5), which responds to different environmental signals including low-Mg 2ϩ , host-derived antimicrobial peptides, and acidic pH (6)(7)(8). Consistently, results from different laboratories showed that SlyA regulates a subset of PhoP-dependent genes, including ugtL and pagC, in Salmonella (2,3,(9)(10)(11). To activate transcription of ugtL, both PhoP and SlyA must bind to its promoter simultaneously (2).…”
mentioning
confidence: 99%